2012
DOI: 10.4081/dr.2012.e5
|View full text |Cite
|
Sign up to set email alerts
|

Granulosis rubra nasi: a rare condition treated successfully with topical tacrolimus

Abstract: A 20 years-old girl presented with multiple asymptomatic reddish vesicles on face for four years. It used to get worse in summer and was associated with localized hyperhidrosis. The lesions were notable for disappearance on diascopy. Histopathology from the vesicle showed mononuclear cell infiltration in the upper dermis, especially around eccrine sweat apparatus, along with dilatation of superficial capillaries and lymphatics. Based on clinical presentation and histopathology, diagnosis of Granulosis rubra na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…At times, afected patients may have associated poor peripheral circulation and hyperhidrosis of the palms and soles [8]. Summer aggravation of lesions is occasionally found [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At times, afected patients may have associated poor peripheral circulation and hyperhidrosis of the palms and soles [8]. Summer aggravation of lesions is occasionally found [8].…”
Section: Discussionmentioning
confidence: 99%
“…Piotr and Katarzyna have described a 14-year-old patient that responded well to low-dose isotretinoin [12], and Kumar et al reported that topical tacrolimus has been effective in decreasing vesicles in a 20-year-old patient who has had GRN [8].…”
Section: Discussionmentioning
confidence: 99%
“…Erythema may gradually extend to involve upper lip, cheeks, and chin with sweat droplets studded over, giving glistening appearance. Small erythematous macules, papules, vesicles, or pustules lesions can also be seen [ 2 , 8 ]. These lesions disappear on diascopy and reappear on relieving pressure [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association with primary palmoplantar hyperhidrosis, acrocyanosis, and poor peripheral circulation was observed. Kumar et al had reported an association with another eccrine gland disorder, hidrocystoma [ 8 ]. Heid et al had reported an association with rhinorrhea [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation